Non-specific Interactions Between Macromolecular Solutes in Concentrated Solution: Physico-Chemical Manifestations and Biochemical Consequences - Hoppe, Travis; Minton, Allen P. (Frontiers in Molecular Biosciences, 2019)
A general thermodynamic formulation of the effect of hard and soft nonspecific intermolecular interactions upon reaction equilibria is summarized. A highly simplified quantitative model for nonspecific intermolecular interaction is introduced. This model is used to illustrate how the magnitudes of attractive and repulsive components of the overall intermolecular interaction, and the balance between them, influence the concentration-dependent properties of a highly concentrated solution of a single macromolecular solute. The properties calculated using the results of computer simulation and an approximate analytical model are found to agree qualitatively with the results of experimental measurements on protein solutions over a broad range of concentration.